Learning Strategies Used By Eleventh Grade Students Of Senior High School Batik 2 Surakarta In Developing Reading Skill - Kusumaningtyas, Etika Dewi; , Prof. Dr. Endang Fauziati, M. Hum; , Drs. Abdillah Nugroho, M. Hum (2014)
The objectives of the research are to describe the types of learning strategies used by the students, to describe the differences of learning strategies among students, and to describe the pedagogical implication of the dominant learning strategy being applied in developing reading skill of students of the eleventh grade of Senior High School Batik 2 Surakarta. The research was conducted in Senior High School Batik 2 Surakarta, from December 2013 to February 2014. It is case study research. The subject of this research was three eleventh grade students of Senior High School Batik 2 Surakarta. The data of this research were collected from several techniques including observation, interview, and document analysis. In analyzing qualitative data, the researcher conducted method of triangulation to examine the data from interview with the result of observation, source of triangulation to examine the information with the document, and the last is theory of triangulation, it is to know the relation among the theories that used in this research toward the data research. First subject of this research used six strategies of meta-cognitive strategies, nine strategies of cognitive strategies and two strategies of socio-affective strategies in developing her reading skill. Second subject used five strategies of meta-cognitive strategies, seven strategies of cognitive strategies and two strategies of socio- affective strategies in developing his reading skill. Third subject employed five meta-cognitive strategies, six cognitive strategies and two strategies of socio-affective strategies in developing reading skill. The three subjects have almost significant differences in using cognitive strategies; the first subject is the only subject that uses translation, imagery and elaboration strategies. And the third subject is the only subject that uses deduction strategies. An auditory representation strategy is used by second and third subject. For meta-cognitive strategies, only first subject who use functional planning and directed attention. Selective attention is only used by second subject. And delayed production is used by second and third subject.